(untitled) (Indonesian Art and Justice Review, 2025)
Feminist art movements in Indonesia have become an important platform for challenging gender norms and advocating for women’s rights and empowerment. This paper examines how Indonesian feminist artists have utilized visual arts to address issues such as gender-based violence, reproductive rights, and the underrepresentation of women in the art world. By analyzing key feminist art exhibitions, performances, and the work of individual artists, the paper explores how art serves as a medium for both personal and collective expressions of resistance against patriarchal structures. Furthermore, it investigates how these art movements intersect with broader social justice efforts, empowering women to challenge societal constraints and call for gender equality in Indonesia.